Sustainable tourism as a driving factor for competitiveness in the olive sector - Silvério, Ana Cristina (2022)
Tourism is facing serious difficulties worldwide due to the global pandemic COVID-19, translating considerably into an industry effort to compete in the marketplace. In effect, sustainable tourism is considered to have a symbiotic relationship with competitiveness that will allow organisations to make a difference. This means that the sustainability factors are positively related to the competitiveness indicators. In this context, as the oliviculture sector faces challenges in a changing market in terms of ecological, demographic, and consumption practices changes, it is considered that sustainable tourism will enable the sector to make a difference. For, the environmental and social changes of the stakeholders enhance the promotion of sustainability to meet their needs, which in turn increases the sector's competitive advantage. In this respect, the present study was based on a literature review consolidated in a bibliometric analysis to analyse sustainable tourism as a driver of competitiveness in the oliviculture industry. For this purpose, the Scopus database was used, in which 157 full articles published until September 2021 were obtained. Based on the results, using the Bibliometrix R, it was found that research in this field has emerged in the last 20 years and focuses particularly on the terms “competitiveness”, “ecotourism” and “tourism development”. In addition, the countries with the highest scientific production and citations, the main sources of publication in this field of research, the documents with the most citations as well as the co-citations between authors were analysed. Through bibliometric analysis, it is possible to provide researchers, policy-makers and managers with a current view of the undoubted role that sustainable tourism plays in the competitiveness of the olive sector. Considering the trends, it is therefore expected to contribute bases for future strategies aimed at overcoming obstacles, overcoming challenges, and seizing opportunities for a more competitive sector.